Pelatihan Pembuatan Video Animasi dengan Aplikasi Animiz untuk Mendukung Pembelajaran Kreatif di Sekolah Dasar - Nurjannah, Nurjannah; Kaswar, Andi Baso; Andayani, Dyah Darma; Dirawan, Gufran Darma; Risal, Andi Akram Nur (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2025)
The training on creating animated videos using the Animiz application at SDN 2 Sinjai aimed to enhance teachers' competencies in developing creative and interactive digital learning media. This activity was conducted on December 16, 2024, through four stages: planning, implementation, observation, and evaluation, using a hands-on training approach combined with intensive mentoring. The results showed that teachers were able to understand the material well, operate the Animiz application independently, and produce animated videos relevant to primary school learning themes. The evaluation indicated that most participants responded very positively regarding the clarity of the material, the relevance of the training, and the ease of using the application. Despite some technical challenges and time constraints, the training was considered effective in improving teachers' motivation and skills in utilizing digital technology. This initiative serves as a strategic first step in promoting digital transformation in primary schools and should be followed up with advanced training and continuous mentoring.